PIVKA-II as a surrogate biomarker for therapeutic response in Non-AFP-secreting hepatocellular carcinoma - San-Chi Chen; Hsiang-Ling Ho; Chien-An Liu; Yi‑Ping Hung; Nai-Jung Chiang; Ming‑Huang Chen; Yee Chao; Muh-Hwa Yang (BMC Cancer)
Abstract Background Alpha-fetoprotein (AFP) is a key biomarker for hepatocellular carcinoma (HCC), but 30–40% of cases are AFP-negative. Prothrombin induced by vitamin K absence II (PIVKA-II) is more sensitive for HCC detection, though its role in systemic therapy remains underexplored. This study aimed to evaluate PIVKA-II in non-AFP-secreting HCC treated with systemic therapy. Methods Patients with unresectable HCC undergoing systemic therapy were enrolled. Baseline imaging and PIVKA-II levels were recorded. After 8–12 weeks of treatment, response was evaluated through imaging and repeat PIVKA-II measurements. Results A total of 116 treatment assessments from 61 cases were analyzed. Baseline PIVKA-II levels correlated with tumor size, but not tumor number or liver function. PIVKA-II regression (≥ 50% reduction) and progression (≥ 50% increase) were defined using ROC analysis. Imaging showed 71.0% objective response in the regression group, 50.0% stable disease in the stable group, and 83.7% progressive disease in the progression group (p < 0.001). This association held for targeted therapies, immune checkpoint inhibitors, and chemotherapy. Progression-free survival (PFS) for the regression, stable, and progression groups was non-reached, 6.7, and 3.2 months (p = 0.0002), and overall survival (OS) was non-reached, non-reached, and 18.5 months (p = 0.02). Conclusions This study is the first to establish the “50–50 rule” for PIVKA-II response in non-AFP-secreting HCC treated with systemic therapy, highlighting its value as a surrogate marker for radiological outcomes and prognosis.